MODERATING EFFECT OF OPERATIONAL LEVERAGE ON THE RELATIONSHIP BETWEEN CORPORATE INVESTMENT AND FIRM PROFITABILITY - Marques, Kelly Cristina Mucio; Hercos Junior, José Braz; Fujihara, Hélio Masaru (Advances in Scientific and Applied Accounting, 2021)
Objective: the aim was analyze how the operational leverage moderates the relationship between corporate investment and profitability of companies listed on brazilian stock exchange. Method: The sample consisted of 114 companies active in stock exchange. Regression with panel data covering the period from 2008 to 2018 was used for data analysis. Static and dynamic models were used. Findings: The main results showed that operational leverage moderates the relationship between investment and ROA, so that the greater the operational leverage and the greater the investment, the greater the ROA. It was also observed that contemporary explanatory variables were more adequate to explain the model. Contributions: The findings indicate that greater operational leverage is an advantage for companies that present growth opportunities and have not reached the point of overinvestment, since ROA decreases as less is invested in this scenario. The research implication is that operating leverage is a factor that must be considered both in investment decisions and in profit forecasting models. This study differs from the previous ones, as it deals with the impact of investment and operational leverage on the contemporary results of companies in a joint manner.